2019
DOI: 10.18280/jesa.520406
|View full text |Cite
|
Sign up to set email alerts
|

Design of Neural Network Based Expert System for Automated Lime Kiln System

Abstract: Rotary lime kiln is an important pulp production facility of paper mills and cement factories. To achieve fully-automated lime kiln production, this paper firstly carries out a thorough review of the production processes of lime kiln, revealing that the shell temperature of lime kiln and furnace oil consumption are two key parameters to the working efficiency and product quality of the kiln. Next, an expert system was designed based on artificial neural network to optimize the parameters in kiln application. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…This has been illustrated in Figure 8. It has been observed that there is a 25% reduction in emission of equivalent Carbon over a three-year period [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been illustrated in Figure 8. It has been observed that there is a 25% reduction in emission of equivalent Carbon over a three-year period [22].…”
Section: Resultsmentioning
confidence: 99%
“…In the later part of the year, Lan [21] also considered an agricultural application and analyzed the sensitivity of consumer's greenness sensitivity, green cost coefficient and stochastic output ratio. During the same year, Anand et al [22] had brought into limelight emissions of greenhouse gases during the design of a neural network for an automated lime kiln plant.…”
Section: Literature Surveymentioning
confidence: 99%
“…A research group used AI to optimize energy consumption and throughput of cement kilns and mills by improving equipment productivity as well as reducing CO 2 emissions. [7] Anand et al [10] showed that the shell temperature of a lime kiln and furnace oil consumption are two key parameters to the working efficiency and product quality of the kiln. So, they designed intelligent controllers based on artificial neural network to optimize the parameters in kiln application.…”
Section: Related Workmentioning
confidence: 99%
“…Goense compared autonomous with conventional vehicles, equipped with implements having working widths from 50 to 120 cm. He showed, if autonomous vehicles are often utilized 23 hours every day, it'd be economically feasible with slight reductions in prices of navigation systems or with slight increases parturient costs [21]. On the other hand, there could even be negative effects within the type of upper costs in traveling distances for service personal.…”
Section: Economics Aspectmentioning
confidence: 99%